2014
DOI: 10.1371/journal.pone.0112817
|View full text |Cite
|
Sign up to set email alerts
|

Maternally Derived Egg Hormones, Antibodies and Antimicrobial Proteins: Common and Different Pathways of Maternal Effects in Japanese Quail

Abstract: Avian eggs contain a variety of maternally-derived substances that can influence the development and performance of offspring. The levels of these egg compounds vary in relation to environmental and genetic factors, but little is known about whether there are correlative links between maternal substances in the egg underlying common and different pathways of maternal effects. In the present study, we investigated genetically determined variability and mutually adjusted deposition of sex hormones (testosterone-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 59 publications
1
13
0
Order By: Relevance
“…Previous results on phenotypic variation are controversial; in the study species, a phenotypic correlation between androgens and immune factors was found at between-but not within-clutch level , see also Gasparini et al, 2007), but multiple other studies find no support for the hypothesis (Groothuis et al, 2006;Hargitai et al, 2009;Ruuskanen et al, 2011). In selection lines for yolk T and behavior (quails, Okuliarova et al, 2014), IgY or lysozyme levels did not respond to selection similarly as T, suggesting no genetic covariation. Thus, a similar (or opposite) response to environmental and social conditions could explain the reported phenotypic correlation between yolk androgens and immune factors also in the study species.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…Previous results on phenotypic variation are controversial; in the study species, a phenotypic correlation between androgens and immune factors was found at between-but not within-clutch level , see also Gasparini et al, 2007), but multiple other studies find no support for the hypothesis (Groothuis et al, 2006;Hargitai et al, 2009;Ruuskanen et al, 2011). In selection lines for yolk T and behavior (quails, Okuliarova et al, 2014), IgY or lysozyme levels did not respond to selection similarly as T, suggesting no genetic covariation. Thus, a similar (or opposite) response to environmental and social conditions could explain the reported phenotypic correlation between yolk androgens and immune factors also in the study species.…”
Section: Discussionmentioning
confidence: 60%
“…Yolk IgY concentration showed a tendency for low to moderate heritability but this was not statistically significant. Previous data from poultry and quail suggest a heritable basis for maternal IgY and lysozyme transfer (Grindstaff et al, 2003;Abdel-Moneim and Abdel-Gawad, 2006;Okuliarova et al, 2014). The lack of significant heritability for yolk IgY concentration may be due to lack of power (given the large s.e.s).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Owing to their high growth and egg-laying rates, Japanese quail have been preferentially bred worldwide, including selective breeding to improve egg and meat production, since the beginning of the 20 th century [1]. As quail farming has increased, studies have examined the genetic diversity of domestic quail populations as well as physiological and genetic factors affecting economic traits, such as growth rate, egg-laying rate, and disease resistance [16]. Japanese quail is also used in several biological studies as a laboratory animal because of its useful biological properties, including a short generation interval and small body size [7,8].…”
Section: Introductionmentioning
confidence: 99%